Conceptualizing factors affecting knowledge transfer between expatriates and host country nationals - Zulkifly, Nurul Afiqah; Ismail, Maimunah (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
This paper intends to examine factors influencing transfer of knowledge between expatriates and host country nationals (HCNs). This conceptual paper reviews literature on knowledge transfer, its relation with expatriates and HCNs, and the factors affecting knowledge transfer involving the two groups of human resources. Transfer of knowledge among terrestrial dispersed and diverse locations has become significant as it is essential in retaining competitive advantage among multinational corporations (MNCs) globally where both expatriates and HCNs co-exist. They function as ‘boundary spanners’ which means that they facilitate the process of knowledge transfer. However, owing to expatriates and HCNs come from different cultural backgrounds, forming a positive relationship between them may face challenges. Existing research has focused on general mechanisms of unidirectional knowledge transfer but not many were conducted specifically on the factors influencing knowledge transfer involving expatriates and HCNs bi-directionally. Therefore, this study attempts to conceptualize factors influencing knowledge transfer between expatriates and HCN bi-directionally.